Species Diversity of Earthworm in the Field of Biology Gadjah Mada University - Sita Ratnawati; Niken Satuti Nur Handayani; Trijoko Trijoko (Jurnal Biologi Universitas Andalas, 2019)
The Earthworms are one of the invertebrate species which hasn’t backbone. The Earthworm has lived in a few habitats, for example in the humid of forest ground with the high density of cover canopy. Field of Biology UGM is an artificial forest and has a high density of cover canopy  and this condition can supported the living habitat of earthworms. The aim of this research were investigated species diversity of earthworm in the field of Biology UGM.. Sampling method was carried out with purposive random sampling method. Result obtained that the earthworms in the field Biology of UGM consist of three species. The Three species were Pheretima hawayana, Pheretima sp., and Eudrilus eugeniae. Data analysis was used UPGMA method by 3.1 MVSP Program and obtained that generally, similarity percentage of P. hawayana, Pheretima sp., dan E. eugeniae interspecies more than 55 %. Whereas similarity percentage of P. hawayana and  Pheretima sp. more than 85 %.